On the viability of gravitational Bose-Einstein condensates as alternatives to supermassive black holes - Hujeirat, Ahmad (Monthly notices of the Royal Astronomical Society, 2012)
Abstract. It is argued that astrophysical Bose-Einstein condensates (BECs) most likely form through a quasi-static contraction of ultradense cores of neutron
Gesehen am 12.11.2018